Additional systematic information on the Early Carboniferous palynoflora from the Ambo Formation, Pongo de Mainique, Peru - Azcuy, Carlos Leopoldo (2006)
Palynologic results presented in this contribution come from six productive samples located in the upper part of the Ambo Formation at Pongo de Mainique, Peru. A brief geologic information and an annotated species list (some illustrated) including taxonomic and morphologic remarks for some taxa (genera or species) and their stratigraphic and geographic occurrences outside Peru, are displayed herein. The lectotype of Verrucosisporites nitidus Playford is here designed. The composition of the palynoflora allows correlating to the Cordylosporites magnidictyus Palynozone (late Viséan of the Amazon Basin, Brazil). More information such as the complete and illustrated list of taxa, are part of a recent publication on the palynology of the same unit realised by the same authors.